Body-size and aerial basking dynamics of the Spiny Softshell (Apalone spinifera) in a human-modified landscape in Tennessee, USA - O'Bryan, Christopher; Hamed, M. Kevin; Laughlin, Thomas F.; Coffey, J. Wallace (Journal of North American Herpetology, 2022)
Spiny Softshells (Apalone spinifera) are found in aquatic environments throughout much of the central-eastern USA. Although this species is widespread throughout much of Tennessee, little is known about Spiny Softshells in the state’s northeastern counties. Further, little work has investigated the role of Spiny Softshell body size on resource use, and the morphometrics of the species in a human-modified ecosystem. Here we present results of a four-month capture and basking observation study conducted in 2004. We investigated whether larger body size was positively associated with presence at limited aerial basking resources that are potentially important for thermoregulation. We found that hoop trap captures positioned next to basking sites, a proxy for aerial basking resource use, were not associated with sex or body size measurements. Opportunistic basking observations revealed most individuals basked in the afternoon. Our study, while short in duration and of low sample size, builds understanding on the body size and intraspecific effects of resource use by Spiny Softshells in a human-modified ecosystem.